THU0085 Il-15 enhances expression of mrna encoding anti-apoptotic protein bcl-xl and triggers proliferation of rheumatoid arthritis fibroblast like synoviocytes. (1st June 2001) - Kurowska, MS; Kontny, E; Janicka, I; Rudnicka, W; Kowalczewski, J; Maslinski, W
Abstract : Background: The hallmarks of rheumatoid arthritis (RA) are leukocytic infiltration of the synovium and expansiveness of fibroblast like synoviocytes (FLS). The abnormal proliferation of FLS as well as their resistance for apoptosis is thought to be mediated, at least in part, by the overproduction of proinflammatory cytokines and growth factors. IL-15, a T-cell growth factor, has been suggested to play an important role in the pathogenesis of RA. In the present study we tested the hypothesis that IL-15 contributes to FLS expansiveness. Objectives: The aim of this study was to: (i) examine whether RA-FLS express all three receptor chains, i.e. IL-15Ra, IL-2Rb and IL-2Rg required for functional IL-15 receptor complex; (ii) investigate the effect of IL-15 on RA-FLS proliferation; and (iii) analyse IL-15 triggered expression of mRNA encoding anti-apoptotic: Bcl-xL and Bcl-2, and proapoptotic Bcl-xS proteins in these cells. Methods: Synoviocytes isolated from synovial membrane of RA patients (cultured for 2–7 passages) or PBMC from healthy donors were stimulated with TNF-a (10 ng/ml), IL-1b (1ng/ml) or IL-15 (25 ng/ml) in medium supplemented with 5% or 0.1% FCS. After 4 h stimulation, levels of mRNA encoding IL-15Ra, IL-2Rb, IL-2Rg, Bcl-2, Bcl-xS and Bcl-xL were analysed by RT-PCR. The expression of surface IL-15Ra was tested using flow cytometry after 24–48 h stimulation. Proliferation of the FLS was determined based on the incorporation of 3H-thymidine after 72 h pretreatment with 0.1% FCS then 24 h stimulation with IL-15 in medium with 0.1% FCS. Results: Human FLS express mRNA encoding IL-15Ra isoforms and IL-2Rb and g chains. Interestingly, TNF-a or IL-1 b trigger significant elevation of mRNA encoding IL-15Ra isoforms (3 times), but not IL-2Rb or g chains. Flow cytometric analysis confirmed the enhancement of IL-15Ra protein expression. The IL-15 receptor complex is functional: IL-15 increased (by ~ 68%) proliferation of FLS in medium with low (0.1%) FSC. Moreover, in these conditions, IL-15 triggers significant elevation of mRNA encoding anti-apoptotic protein Bcl-xL, while the pro-apoptotic Bcl-xS remained unchanged. However, unlike in PBMC, IL-15 fails to rise the level of anti-apoptotic bcl-2 mRNA in FLS. Conclusion: Our studies indicate that IL-15, via enhancement of anti-apoptotic Bcl-xL and increased proliferation is, at least in part, responsible for expansive behaviour of FLS.